Thyroid function disorders and secondary cancer following haematopoietic stem cell transplantation in pediatrics: State of the art and practical recommendations for a risk-based follow-up - Cattoni, Alessandro; Molinari, Silvia; Riva, Benedetta; Di Marco, Santo; Adavastro, Marta; Faraguna, Martha Caterina; Garella, Vittoria; Medici, Francesco; Nicolosi, Maria Laura; Pellegrinelli, Claudia; Lattuada, Martina; Fraschini, Donatella; et al. (Frontiers in Endocrinology, 2022)
Thyroid disorders (TD) represent a remarkable share of all the late morbidities experienced following pediatric haematopoietic stem cell transplantation (HSCT), with long-term reported occurrence often exceeding 70%. In addition, the data collected on wide cohorts of survivors assessed longitudinally outlined a progressive increase in the cumulative incidence of TD as far as 30 years following transplantation. Accordingly, a life-long monitoring of thyroid health is warranted among patients exposed to HSCT in childhood, in order to early detect TD and undertake a prompt dedicated treatment. Although several national and international consortia have provided recommendations for the early detection of thyroid disorders among childhood cancer survivors exposed to radiotherapy and alkylating agents, no guidelines specifically and thoroughly focused on HSCT-related TD have been published to date. As stem cell transplantation has become the standard-of-care in a growing body of non-oncological conditions, this urge has become pivotal. To highlight the challenging issues specifically involving this cohort of patients and to provide clinicians with the proposal of a practical follow-up protocol, we reviewed published literature in the light of the shared experience of a multidisciplinary team of pediatric oncologists, transplantologists, pathologists and endocrinologists involved in the long-term care of HSCT survivors. As a final result, we hereby present the proposals of a practical and customized risk-based approach to tailor thyroid health follow-up based on HSCT-related detrimental factors.